Postharvest biochemical and physiological characterisation of imported avocado fruit - Donetti, Manuela (Cranfield University, 2011)
Difficulties in controlling and forecasting avocado fruit ripening and the highly perishable nature of the crop once harvested, are the major causes of concern for avocado traders. In particular, the simultaneous presence of many suppliers may account for increased fruit variability during ripening. Avocado is a climacteric fruit with consistent ethylene production after harvest which is also related to high perishability. However, the mechanisms regulating ethylene biosynthesis and mesocarp softening are not completely understood. In order to study such effects, avocado fruit from different growing areas and harvested at various maturity stages, were investigated and the biochemical and physiological changes during ripening at both 18 and 23°C were studied. Mesocarp softening and fatty acid content discriminated fruit maturity and growing area, respectively, whereas C7 sugars (D-mannoheptulose and perseitol) discriminated length of fruit shelf life. For the first time, oleic acid content presents in the oil mesocarp was found to depend on fruit sources making of this a suitable indicator of avocado fruit growing area. In contrast, sugar content declined along fruit maturity and ripening. In particular the mannoheptulose presents in avocado mesocarp might be use to estimate avocado fruit shelf life. Indeed, fruit harvested late in season were found to have a lower C7 content than earlier harvest fruit and a faster softening, regardless fruit source. However, sugars content changed between growing area, thus a general C7 threshold defining fruit storability seems to be not definable. Furthermore, other possible indicators of fruit maturity and/or ripening stage have been searched in the cell wall constituents of avocado mesocarp. Thus, the structural carbohydrates profile of avocado mesocarp investigated with a new immunological method changed during ripening and harvest time (early and late season), suggesting a possible effect of cell wall composition on fruit ripening regulation. Also, the possible use of ethylene application in reducing the high heterogeneity noted on imported fruit from South Africa was also evaluated through different consignments. Results showed ethylene efficacy changed depending on harvest time and fruit dimension with less efficacy of the treatment on fruit harvested at the end of the season and characterised by smaller size.One of the most commercialized avocado cultivars, Hass, is peculiar in that its skin colour changes from green to deep purple as ripening progresses. The most common ripening indicator of avocado fruit is the mesocarp firmness and the destructive nature of this evaluation increases losses in the avocado industry. The availability of a non-destructive indicator of fruit ripening represents an important advantage for avocado consumers and importers. Thus, the possible relationship between mesocarp softening, skin colour were objectively evaluated (C*, L*, and H°), and the main pigment, cyanidin 3-O-glucoside, was investigated. Cyanidin 3-Oglucoside was confirmed to be the main anthocyanin present in avocado cv. Hass peel, regardless of preharvest factors. However, differences in its content were noted between shelf life temperatures. A higher relationship between hue angle and firmness was detected in late harvest fruit, whereas no correlation was found between anthocyanin content and firmness. Avocado skin is also involved in defence mechanisms due to the presence of antifungal and phenolic compounds. These phenolic compounds represent a natural protection against pathogenic infections and seem to be down regulated during ripening. The main phenolics were identified and quantified, using a new analytical method which was validated and optimised. Epicatechin, chlorogenic acid and procyanidin B2 were found to be present in the skin tissue and quantified using this assay and found to vary during shelf life and seasons. Although phenolics were present in minor amounts, in avocado pulp they are involved in mesocarp discoloration incidence, and therefore with fruit postharvest quality. Due to a lack of information, a new straightforward method for the identification and quantification of the main phenolics present in avocado mesocarp was developed. Finally, a commercial trial was undertaken to ensure that the results obtained in the laboratory can be reproduced in the market place. In conclusion, postharvest markers can define avocado fruit maturity and growing area and give guidelines in the control of avocado shelf life. Moreover, new methods for the investigation of the phenolic profiles (peel and mesocarp) and the characterisation of cell wall structures can be further tools in the management of avocado fruit postharvest quality.
Keywords: firmness; colour; fatty acids; sugars; ethylene; cell wall composition